2022
DOI: 10.3390/electronics11050776
|View full text |Cite
|
Sign up to set email alerts
|

Trust-Based Recommendation for Shared Mobility Systems Based on a Discrete Self-Adaptive Neighborhood Search Differential Evolution Algorithm

Abstract: Safety is one concern that hinders the acceptance of ridesharing in the general public. Several studies have been conducted on the trust issue in recent years to relieve this concern. The introduction of trust in ridesharing systems provides a pragmatic approach to solving this problem. In this study, we will develop a trust-aware ridesharing recommender system decision model to generate recommendations for drivers and passengers. The requirements of trust for both sides, drivers and passengers, are taken into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The merge of model-based collaborative filtering methods with trust relationships to improve the accuracy of recommendations has recently become a very popular research topic, especially using the matrix factorization technique due to its high precision and ease of use contribution to alleviating the problem of sparsity data better than other techniques [3,8]. Many researchers have exploited this technique to learn about latent features of users and well-known ratings items, and to merge social relationships between users with rating data using different techniques.…”
Section: Literature Review Of Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The merge of model-based collaborative filtering methods with trust relationships to improve the accuracy of recommendations has recently become a very popular research topic, especially using the matrix factorization technique due to its high precision and ease of use contribution to alleviating the problem of sparsity data better than other techniques [3,8]. Many researchers have exploited this technique to learn about latent features of users and well-known ratings items, and to merge social relationships between users with rating data using different techniques.…”
Section: Literature Review Of Related Workmentioning
confidence: 99%
“…Many researchers have exploited this technique to learn about latent features of users and well-known ratings items, and to merge social relationships between users with rating data using different techniques. The researchers proposed in [8] a "SoRec" model which integrates a social network database into a probability matrix factorization model by simultaneously analyzing the rating matrix and the social trust matrix by sharing the matrix of features latent to a user [10]. Their empirical analysis shows that their method is superior to the basic matrix factorization model and other memory-based methods that take advantage of trust relationships, but that true recommendation processes are not reflected in this model.…”
Section: Literature Review Of Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…[24]. The incorporation of social preferences into ridesharing decisions was studied by Saisubramanian et al in [25] and the consideration of trust in the ridesharing system was studied by Hsieh in [26]. A study on sharing rides with friends was available in the work [27] by Bistaffa et al A review of user behaviors/characteristics as well as social-economic impacts of the shared transport mode was available in the paper [28] by Sun et al Recent developments in studies on ridesharing can be found in the paper [29] by Hyland and Mahmassani. Although cities may benefit from ridesharing, stakeholders such as drivers and riders may adopt the ridesharing transport mode for a variety of reasons.…”
Section: Introductionmentioning
confidence: 99%